Peningkatan Kualitas Mengajar Dosen Fakultas Hukum Universitas Al Azhar Indonesia Melalui Pelatihan Experiental Learning dan Pembaruan Kurikulum MBKM - Muhammad Khutub; Yusup Hidayat (Universitas Al Azhar Indonesia, 2022)
The MBKM program initiated by the Ministry of Education and Culture in the past year has had an impact on the teaching and learning process of lecturers at the Faculty of Law at UAI. The existence of the MBKM program makes the Faculty of Law in collaboration with Vrije University hold Experiential Learning training for all permanent and non-permanent lecturers, as an effort to improve the quality of lecturer learning. This study uses a descriptive-qualitative method and a questionnaire-based Spearman's Coefficient with 20 permanent and non-permanent lecturers as respondents in the Faculty of Law UAI. FH UAI also realizes that MBKM and Experiential Learning are expected to have a significant impact on the quality of the profile of graduates as candidates for superior and useful human resources in society and the world of work, of course, it takes time and a process that is not simple to implement and achieve results. optimal. The implementation of MBKM and Experiential Learning still leaves several problems that become challenges for teachers in particular and need to be faced together with related parties both within Al-Azhar University Indonesia, government agencies and relevant partners.Keywords – Lecturer, Experiental learning training, MBKM, Fakultas hukum UAI.